2021
DOI: 10.3389/fonc.2021.664848
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mutated p53 Dependency in Triple-Negative Breast Cancer Cells Through CDK7 Inhibition

Abstract: BackgroundCyclin-dependent kinase 7 (CDK7) is crucial for cell cycle progression and gene expression transcriptional regulation, which are often not assessed in cancer developing process. CDK7 inhibitors have emerged as promising drugs for treating diverse cancers, including breast cancer. However, the mechanism behind its anticancer effect has not been well investigated. Here, the possible mechanism of CDK7 inhibitors for treating human triple-negative breast cancer (TNBC) has been studied.MethodsThe effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…As shown in Figures 2A,B , the group with CDK7 shRNA vectors displayed decreased cell proliferation and fewer colony spots than the control group. In our exploration of the regulatory mechanism, expression levels of p53, a downstream effector of CDK7 ( Figures 2C,D ), indicated that CDK7 inhibition increased the p53 protein levels, confirming previous results ( Peng et al, 2021 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Figures 2A,B , the group with CDK7 shRNA vectors displayed decreased cell proliferation and fewer colony spots than the control group. In our exploration of the regulatory mechanism, expression levels of p53, a downstream effector of CDK7 ( Figures 2C,D ), indicated that CDK7 inhibition increased the p53 protein levels, confirming previous results ( Peng et al, 2021 ).…”
Section: Resultssupporting
confidence: 89%
“…To explore the effect of CDK7 inhibitors on breast cancer cells, we measured the viability of MCF-7 cells after incubation with increasing concentrations of THZ1 and LDC4297 for 24 and 48 h. The CCK8 results showed that although the survival of MCF-7 cells was not significantly affected by treatment with low concentrations of THZ1, the repressive effect could still be detected in a dose- and time-dependent manner, confirming previous results ( Peng et al, 2021 ). As shown in Figure 1A , LDC4297 also suppressed tumor growth.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This combination therapy is therefore not effective in p53-deficient cells. Moreover, CDK7 inhibition also reduced the expression of mutant p53 in TNBC cells, while upregulating WT p53 in ER+ breast cancer cells, although the exact mechanism underlying this potential selectivity remains elusive [ 103 ]. Similar to interactions with p53 and BRD4, CDK8 binds to p53 target genes and is a co-activator of the p53 transcriptional program in response to p53-activating stimuli [ 104 ].…”
Section: Tp53 Loss In Tnbc and Sensitivity To Tmi’smentioning
confidence: 99%
“…Although THZ1 has been demonstrated to suppress triple-negative breast cancer (TNBC), its anticancer effect on non-TNBC breast cancer cells, including MCF-7 and ZR-75-1 cells, is still controversial [ 12 , 13 ]. We previously reported that a low THZ1 concentration mainly repressed MCF-7 cell proliferation rather than induced cell death [ 14 , 15 ]. Therefore, strategies that decrease the survival and trigger the death of wild-type (WT) p53 breast cancer cells at low THZ1 concentrations might contribute to breast cancer therapy.…”
Section: Introductionmentioning
confidence: 99%